The civic culture political attitudes and democracy in five nations - Almond, Gabriel A. (Gabriel Abraham) 1911-2002; Verba, Sidney (Princeton legacy library, 1963)
The authors interviewed over 5,000 citizens in Germany, Italy, Mexico, Great Britain, and the U.S. to learn political attitudes in modem democratic states.Originally published in 1963.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905